Successful treatment of Leuconostoc bacteremia in a neutropenic patient with tigecycline - Trupti Patel; Aoife Molloy; Robin Smith; Indran Balakrishnan (MDPI AG, 2012)
Leuconostoc lactis is a recognised cause of infection in immunocompromised hosts. It is intrinsically resistant to multiple antibiotics and treatment options may be limited. We report the safe and effective use of tigecycline in the treatment of Leuconostoc catheter-related line sepsis in a neutropenic patient. To our knowledge, this is the first reported case of successful use of tigecycline for Leuconostoc bacteremia.